INFLUENCE OF SERVICE QUALITY AND SCHOOL IMAGE ON SATISFACTION AND ITS IMPLICATIONS TOWARDS LOYALTY OF STUDENTS SMK PGRI 35 JAKARTA - Rusdi, Muhamad; Mochamad Mukti Ali (Dinasti Publisher, 2020)
The purpose of this study was to determine the effect of service quality, school image on the satisfaction and loyalty of students of SMK PGRI 35 Jakarta. The population used in this study were students of SMK PGRI 35 Jakarta with a total sample of 160 respondents. Data were collected through a questionnaire using a Likert scale. The data analysis of this research used SEM with Lisrel. The research results show that service quality and school image have a positive and significant effect on satisfaction and loyalty, and satisfaction has a positive and significant effect on loyalty. In addition, the results of this research indicate that without going through the intervening variables, it will directly have a higher effect value than indirectly.